Dyslipidaemia in a Black African Diabetic Population: Burden, Pattern and Predictors - Lumu, William; Kampiire, Leaticia; Akabwai, George Patrick; Ssekitoleko, Richard; Kiggundu, Daniel Ssekikubo; Kibirige, Davis (BMC research notes, 2017)
This study sought to assess the burden, pattern and predictors of dyslipidaemia in 425 adult diabetic patients in Uganda. The median (IQR) age of the study participants was 53 (43.5–62) years with a female majority (283, 66.9%). Dyslipidaemia defined as presence of ≥ 1 lipid abnormalities was observed in 374 (88%) study participants. Collectively, the predictors of dyslipidaemia were: female gender, study site (private hospitals), type of diabetes (type 2 diabetes mellitus), statin therapy, increased body mass index and diastolic blood pressure. Proactive screening of dyslipidaemia and its optimal management using lipid lowering therapy should be emphasised among adult diabetic patients in Uganda.
Keywords: Dyslipidaemia; Burden; Adult diabetics; Predictors